A historical institutionalist perspective on the persistence of state controls during financial sector reforms: the insightful case of Myanmar. Issue 1 (28th August 2020) - Win, Sandar; Kofinas, Alexander
Abstract : Purpose: Many transition economies are former socialist planned economies and have undergone market reforms of their financial sector to signal their transition towards democracy. However, governments in these countries have been reluctant to relinquish the pre-existing controls on economy and have adopted nuanced and sophisticated approaches to retain control. In such context, scholars may find it challenging to investigate the role played by the state in the success or failure of attempted market reforms. This work investigates the different forms of state-induced accounting controls that may preserve the status quo within the economy during transition, using Myanmar as an example. Design/methodology/approach: The authors adopted a longitudinal qualitative research method aiming to reveal the very processes and mechanisms used by the banks and their evolution over time. This method is in accordance with the historical institutionalist perspective that they have applied within this research. Findings: The authors found that the Myanmar government embarked on the privatisation of their financial sector from 1990 to 2016 as a major public sector reform initiative. Under the guise of market reforms, it used both state-led and market-led controls to emulate and retain the socialist banking model where banks are used to fund the immediate government's budget deficits. This created a series of intended and unintended consequences, resulting in the ultimate failure of the government's market reforms. Research limitations/implications: Previously, research on public sector management accounting in emerging economies was not relying consistently on using theory. The relative limited theorisation led to gaps when attempting to understand and explain the opaque forms of state control mechanisms in transition economies. By applying historical institutionalist perspective, and a more theory-driven, reflective approach to the interpretation of the data collected, the authors have provided a deeper insight and understanding on how different forms of state controls can emerge, adapt and persist in transition economies such as Myanmar. Practical implications: The authors demonstrated that though the state may have implemented market reforms to signal regimes change, this does not necessarily mean that the government has relinquished their control on the economy. The state could take a more sophisticated, covert approach towards state controls leading to both intended and unintended consequences. Thus, even if the state's preferences change, the decisions cannot be easily reversed, as path-dependent state controls may have become pervasive affecting any further institutional and policy developments. Thus, the authors suggest that governments in both transition and developed economies should be cautious when enacting regulations on corporate control. Originality/value: In this paper, the authors have applied a historical institutional perspective in their analysis instead of the more widely used sociological, institutionalist approach. This allowed authors to harness rich longitudinal data indicating that market reforms and their success or failure should be examined as an ongoing process rather than a completed action. This is especially important in transition economies where the state may be unwilling to renounce the existing controls on the industry and may resort to more opaque forms of state control, eventually obstructing the intended reforms.